Complement component C1q is produced by isolated articular chondrocytes. Issue 5 (May 2020) - Lubbers, R.; van Schaarenburg, R.A.; Kwekkeboom, J.C.; Levarht, E.W.N.; Bakker, A.M.; Mahdad, R.; Monteagudo, S.; Cherifi, C.; Lories, R.J.; Toes, R.E.M.; Ioan-Facsinay, A.; Trouw, L.A.
Summary: Objective: Inflammation and innate immune responses may contribute to development and progression of Osteoarthritis (OA). Chondrocytes are the sole cell type of the articular cartilage and produce extracellular-matrix molecules. How inflammatory mediators reach chondrocytes is incompletely understood. Previous studies have shown that chondrocytes express mRNA encoding complement proteins such as C1q, suggesting local protein production, which has not been demonstrated conclusively. The aim of this study is to explore C1q production at the protein level by chondrocytes. Design: We analysed protein expression of C1q in freshly isolated and cultured human articular chondrocytes using Western blot, ELISA and flow cytometry. We examined changes in mRNA expression of collagen, MMP-1 and various complement genes upon stimulation with pro-inflammatory cytokines or C1q. mRNA expression of C1 genes was determined in articular mouse chondrocytes. Results: Primary human articular chondrocytes express genes encoding C1q, C1QA, C1QB, C1QC, and secrete C1q to the extracellular medium. Stimulation of chondrocytes with pro-inflammatory cytokines upregulated C1QA, C1QB, C1QC mRNA expression, although this was not confirmed at the protein level. Extracellular C1q bound to the chondrocyte surface dose dependently. In a pilot study, binding of C1q to chondrocytes resulted in changes in the expression of collagens with a decrease in collagen type 2 and an increase in type 10. Mouse articular chondrocytes also expressed C1QA, C1QB, C1QC, C1R and C1S at the mRNA level. Conclusions: C1q protein can be expressed and secreted by human articular chondrocytes and is able to bind to chondrocytes influencing the relative collagen expression.